1992
DOI: 10.1002/per.2410060207
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of longitudinal research to a cognitive theory of adjustment to aging

Abstract: In agreement with Costa and McCrae (1992), the principle of ‘multiple uses’ of longitudinal studies is stressed based on a comparative review of the history of the Berkeley longitudinal studies and their different uses, and of those of the Bonn Longitudinal Study on Aging (BOLSA). Of the many uses of BOLSA, its contribution to the testing of a cognitive theory of aging is discussed. A selection of the findings of BOLSA and other studies of the Bonn Department of Psychology and the Institute of Gerontology, Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 35 publications
2
11
0
1
Order By: Relevance
“…Furthermore, the appraisal or evaluation of the event as desirable versus undesirable, as challenging versus threatening, as controllable versus not controllable will determine whether there will be a lasting influ-ence (Krause, Jay & Liang, 1991;Lazarus & Folkman, 1984). Considering the appraisal of past events is consistent with Thomae's (1980Thomae's ( , 1992 cognitive theory of adjustment to aging. According to this theory, the perception of life events is essential for understanding adaptation.…”
Section: The Past As a Determinant Of Resourcessupporting
confidence: 81%
“…Furthermore, the appraisal or evaluation of the event as desirable versus undesirable, as challenging versus threatening, as controllable versus not controllable will determine whether there will be a lasting influ-ence (Krause, Jay & Liang, 1991;Lazarus & Folkman, 1984). Considering the appraisal of past events is consistent with Thomae's (1980Thomae's ( , 1992 cognitive theory of adjustment to aging. According to this theory, the perception of life events is essential for understanding adaptation.…”
Section: The Past As a Determinant Of Resourcessupporting
confidence: 81%
“…With this in mind, we believe that this study may provide fresh data on the understanding of AtA, and that it is an important contribution to the underdeveloped potential of AtA in older populations (Jopp & Rott, 2006;Thomae, 1992). Firstly, this study contributes with an integ rated model that encompasses a broad range of factors including not only sociodemographic, health, and lifestyle ones, but also SWB and SOC.…”
Section: Please Scroll Down For Articlementioning
confidence: 94%
“…AtA was initially defined by Cattell (1950) as the goodness of internal arrangements by which an adaptation is maintained. Thomae (1992) suggested that AtA is achieved when a balance between the person's cognitive and motivational systems has been attained. Furthermore, a model that represented the nature of development and aging-with the focus on adjustment-was developed in more recent years (Baltes & Baltes, 1990;Baltes & Carstensen, 1996).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the theory of personality in the process of ageing and old age by Neugarten (1964) and the cognitive theory of personality and ageing by Thomae (1992), it is old people that build the image of their old age. In the assumption accepted by Neugarten, the type of adaptation to old age draws the direction of the old person's activeness.…”
Section: Old Age and The Attempts Of Its Re-readingmentioning
confidence: 99%